Synthesis of 7-Arylpurines from Substituted Pyrimidines - Sebris, Armands; Novosjolova, Irina; Turks, Māris (Synthesis, 2022)
A simple three-step approach for the synthesis of substituted N7-arylpurines with an overall yield of the whole sequence from 40% to 71% is described. N7-Arylpurines were constructed by de novo synthesis from commercially available substituted 4-chloropyrimidine-5-amines. Different substituents at purine C2 and C6 were obtained by changing the corresponding substituents of the starting pyrimidine. Further, heteroaromatic, electron-deficient, and electron-rich aromatic groups were attached to the exocyclic amino group by iodane reagents under copper catalysis. This moiety is prepared to become purine N7 position after the ring closure. Finally, purine C8 substitution was varied during the last step of the developed sequence by employing different reagents for the purine ring closing reactions or post functionalization.
Keywords: purines; pyrimidines; copper-catalyzed arylation; iodanes; de novo synthesis; imidazole ring closing